SISTEM INFORMASI GEOGRAFIS WISATA DAN EVEN WISATA KABUPATEN PEKALONGAN BERBASIS ANDROID - Kevin Haritsi Manggala; Ahmad Khambali; Edy Subowo (Jurnal Surya Informatika: Membangun Informasi dan Profesionalisme, 2019)
The purpose of this research is to build Pekalongan Regency Tourism Geographic Information and Tourism Event System application based on android that can facilitate Pekalongan regency community in knowing tourist attractions in Pekalongan regency and upcoming tourism events. The absence of an integrated system regarding tourist attractions and tourism events makes people less aware of the location of tourist objects and tourism events to be held, therefore a system is needed to display information about tourist maps containing the location of tourist attractions, user locations and travel routes to tourist attractions and upcoming tourism events. In developing this system, the author uses the waterfall system development method. This system uses the Google API to display tourist maps, and uses the Java programming language from the Android Studio platform and uses cloud firestore from Firebase. The conclusion of the results of this study is that the Tourism and Event Geographic Information System Application of Pekalongan Regency can help facilitate the public in knowing the location of tourism and upcoming tourism events.